The Impact of the School Social Environment on the Formation of Islamic Character of Students at SD Negeri 2 Pegulon - Annisa, Dita Nur; Shanie, Arsan (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze the influence of the school's social environment on the formation of Islamic character among elementary school students. The Islamic character in question includes values such as religiosity, honesty, discipline, and responsibility. This research employed a descriptive qualitative approach with participants consisting of an Islamic Education (PAI) teacher, a fourth-grade homeroom teacher, and three fourth-grade students at SD Negeri 2 Pegulon. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the school's social environment significantly contributes to the development of students' Islamic character through teacher role modeling, religious routines such as congregational prayer, and positive peer interactions. However, character development also faces challenges from external factors such as inconsistent family environments and peer influences outside school that do not align with Islamic values. In conclusion, strong collaboration between schools, teachers, parents, and the broader social environment is essential to creating a conducive atmosphere for the holistic and sustainable internalization of Islamic values.Keywords: Social environment, Islamic character, Elementary School, Islamic education, Social interaction